Assessing vegetation cover changes of Kuala Lumpur vacant land using NDVI technique - Mohamad Selamat, Izyan Ayuni; Maruthaveeran, Sreetheran; Mohd Yusof, Mohd Johari; Shahidan, Mohd Fairuz (Springer Nature, 2024)
Intense changes in urban land in cities worldwide are among the factors that contribute to diminishing forest land and biodiversity loss. Vegetative cover of diverse species and structures is crucial in ecosystem functions such as carbon storage, carbon sequestration, and stormwater attenuation. Conversely, rapid forest loss causes irreversible environmental degradation, reducing the capacity of these benefits. As reported in several previous studies, the presence of an abundance of vegetation on vacant urban parcels can host many ecological functions. Opportunities to expand urban green spaces by identifying vacant land with increased vegetative cover as potential areas for urban greening should thus, ideally, be fully exploited. Kuala Lumpur is among the fast-growing cities in Southeast Asia, with shrinking natural vegetation cover as the city’s existing vacant land is increasingly decimated via transformation into built areas. The vacant land that still remains is left idle due to topographical limitations or held for strategic reasons. Hence, this study aimed to assess vegetation cover changes within Kuala Lumpur's vacant land during 2018–2021, using the Normalised Difference Vegetation Index (NDVI) technique. The results revealed that 65.4% of the plots show accretion in vegetative cover, indicating the potential of these parcels to be conserved for ecological functions. The findings of this study will assist relevant authorities in identifying areas with vegetative cover accretion for prioritisation of conservation efforts. It is also hoped that this study will prompt the development of tools to assess the ecological values of vacant land on the ground as the next step in urban green space conservation efforts.